India, Latin America, and the Caribbean During the Cold War [Índia, América Latina E Caribe Durante a Guerra Fria] - Ross-Orellana, C (2013)
In this period, the key to the relationship between India and Latin America and the Caribbean (LAC) was based in the political nature of this liaison: it was a "uni-multilateral" relationship, centered in India, where LAC countries operated as a group of autonomous entities (an "island chain" structure), and not as a unit of a supranational character with unified international conduct (an island structure). As we will see, faced with uniform and consistent Indian policies, LAC had national policies which make it impossible to discuss a regional policy towards India. The goal of this work is to form a general characterization of the bilateral policies during the period of the Cold War with the intent of identifying the key explanatory factors of the process. While this may be a limited objective, it addresses the non-existence of an academic debate surrounding the topic. We intend to contribute an analysis which in this phase is primarily descriptive.